2018
DOI: 10.1002/jlb.mr1117-457r
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34, a comprehensive review

Abstract: IL-34 is a novel cytokine that was identified in 2008 in a comprehensive proteomic analysis as a tissue-specific ligand of CSF-1 receptor (CSF-1R). IL-34 exists in all vertebrates including fish, amphibians, birds, and mammals, showing high conservation among species. Structurally, IL-34 belongs to the short-chain helical hematopoietic cytokine family but shows no apparent consensus structural domains, motifs, or sequence homology with other cytokines. IL-34 is synthesized as a secreted homodimeric glycoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 149 publications
(472 reference statements)
3
124
0
Order By: Relevance
“…As a newly identified cytokine, IL-34 is produced by a wide range of cells and participates in the survival, proliferation and differentiation of various cells. 12,13 Currently, the expression of IL-34 is identified as increase in patients with infection of various viruses, including HIV, 33 influenza A virus 34 and HCV. 35 15 Importantly, the increased IL-34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non-alcoholic fatty liver disease and chronic hepatitis C. 35,36 Besides these, IL-34 is shown to increase in different tumour cells, 26,[37][38][39] and related to the prognosis of various cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a newly identified cytokine, IL-34 is produced by a wide range of cells and participates in the survival, proliferation and differentiation of various cells. 12,13 Currently, the expression of IL-34 is identified as increase in patients with infection of various viruses, including HIV, 33 influenza A virus 34 and HCV. 35 15 Importantly, the increased IL-34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non-alcoholic fatty liver disease and chronic hepatitis C. 35,36 Besides these, IL-34 is shown to increase in different tumour cells, 26,[37][38][39] and related to the prognosis of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, collective evidence has demonstrated that IL-34 is involved in the development of viral infection, autoimmune diseases and cancers. 12,13 Importantly, recent studies show that IL-34 is involved in the HBV infection and associated with liver fibrosis. 14,15 Besides, the report from Zhou S et al shows that increased IL-34 is related to the poor survival and tumour recurrence in HCC patients, and modulates the invasion and metastasis of HCC cells via macrophages.…”
Section: Hepatitis B Virus (Hbv) Is One Of the Most Vital Aetiologicamentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, IL‐34 can promote the survival, proliferation and differentiation of mononuclear phagocytic lineage cells, including monocytes, macrophages, dendritic cells, Langerhans cells, osteoclasts, Kupffer cells, and microglia, providing crucial foundation for the role of IL‐34 in the process of immunoregulation in various disorders, including autoimmune diseases, inflammation, cancers and so on . Our previous studies have demonstrated that serum IL‐34 levels were significantly elevated in patients with RA as well as SLE, and the levels were associated with disease activity .…”
Section: Discussionmentioning
confidence: 97%
“…flammation, cancers and so on. 18 Our previous studies have demonstrated that serum IL-34 levels were significantly elevated in patients with RA as well as SLE, and the levels were associated with disease activity. 12,15 In addition, a recent study showed that serum IL-34 levels in patients with SSc were significantly higher than in healthy subjects.…”
Section: Correlations Between Serum Levels Of Il-34 and Hematologicmentioning
confidence: 93%